Quality of life and adherence to antiretroviral therapy in Southern Brazil - Zubaran, Carlos; Medeiros, Gregory; Foresti, Katia; May, William; Michelim, Lessandra; Madi, José Mauro (AIDS care, 2014)
The absence of or limited adherence to treatment is the main cause for the failure of Highly Active Antiretroviral Therapy (HAART). In Brazil, adherence to antiretroviral therapy has been lower than the recommended levels. Although HAART may produce adverse reactions, failure to comply with it may aggravate patients' health status and impair Quality of Life (QoL). The QoL of individuals living chronically with HIV and AIDS has been considered one of the main treatment outcomes. This study is part of a 225-day prospective trial in which participants were enrolled in two different modalities of follow-up: the usual model medical follow-up or an intervention based on the Medication Adherence Training Instrument (MATI). The WHOQOL-HIV BREF questionnaire was used to evaluate QoL of research participants in both groups on the 15th and 225th days of follow-up after the baseline assessment. The result of this study revealed no significant differences of WHOQOL-HIV BREF scores between participants allocated to MATI and non-MATI groups in the first assessment. However, there was a significant difference between the scores obtained on the 15th and 225th days in the domain related to spirituality and personal beliefs irrespective of the modality of follow-up. Other domains of the WHOQOL-HOV BREF remained unchanged. These results indicate that, in this sample, personal beliefs and spirituality may be relevant subjects to explain sustained levels of adherence to HAART.